Perancangan Mesin Penghalus Tanah Liat dan Pencetak Bata Merah Press MRH Khusus Industri Rumahan - Maulana Akbar Pambudi; Fipka Bisono; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
Mojotamping Village is the center of the brick industry in East Java. In this village, almost 90% of the residents work as red brick makers on a home industry scale. However, the manufacturing process still uses less efficient methods. Based on these problems, a design for a clay smoothing machine and MRH red brick press specifically for home industries was created. The method used is the Ulrich method by creating 3 different design concepts by considering the specified criteria. Machine design begins with calculating machine component elements from the selected design concept as a reference in determining the size and material of the components for the clay smoothing machine and MRH red brick press machine specifically for the home industry, then designing what manufacturing processes are needed in making the clay smoothing and printing machine MRH red brick press specifically for home industries. This machine has a printing capacity of 300 bricks per hour, so if the operator runs this machine for 8 hours per day this machine can produce 2500 bricks per day. This machine is designed to use a 3 HP engine which is considered to have good fuel efficiency so it can reduce production costs when compared to existing products.